Empirical study on the use of Pleco for improving Chinese character instruction: the perception of non-native learners of Chinese / Goh Ying Soon - Goh, Ying Soon (Universiti Teknologi MARA, Terengganu, 2016)
This study was an attempt to find out whether engaging in the use of Pleco affects Chinese character acquisition of non-native Chinese learners or not. The study was conducted on the beginning level students at UiTM (Terengganu) in Malaysia. To accomplish the purpose of the study, the researchers chose a sample of 86 subjects, who were taking Chinese beginner and intermediate courses. Then, the subjects participated in the classroom activity using Pleco as a mean to Chinese character learning. The subjects were asked to fill up online questionnaire on their gain during this activity. The result indicated that there was a positive perception among the learners. It was concluded that the subjects who participated in Pleco classroom activity for Chinese characters learning, perceived that this activity can assist them to learn Chinese character better.